Implementation of Merdeka Belajar Policy: Constraints in the Pancasila Students Profile Strengthening Project - Walukow, Maria R.; Naharia, Orbanus; Wullur, Mozes N.; Sumual, Shelty D.M.; Monoarfa, Haris (International Journal of Multidisciplinary Approach Research and Science, 2023)
This paper aims at providing information on how the implementation of Merdeka Belajar policy in Schools is, with a focus on describing the constraints encountered in the Pancasila students profile strengthening project (P5). This project is a learning innovation in the Kurikulum Merdeka. P5 intends to produce education that is more independent and innovative, so that students have competence, Pancasila character and are able to compete globally. In fact, there are still a number of important issues to be studied. This research was conducted at SMAN 1 Tomohon which implements the Kurikulum merdeka independently for the 2022-2023 school year. This qualitative research was designed using the Case Study method which aims at observing what the constraints that exist in the implementation of P5 at SMAN 1 Tomohon are. Data collection was based on questionnaires given to 25 teachers teaching in Grade X. There were 14 study groups and 15 subjects in the Kurikulum Merdeka. The data collected through observation, interviews and document studies is verified and presented as a conclusion. Based on this research, it was found that there were obstacles to educators, schools and students in implementing P5. The Kurikulum Merdeka is designed as an effort to restore Indonesian education and transform learning to a higher quality. Therefore, the constraints in one Content of the Merdeka Belajar Policy, namely the implementation of the Kurikulum Merdeka P5 which is at this early stage, may be used as evaluation material, so that a strategic solution plan can be prepared.